2015
DOI: 10.1007/s13149-015-0425-6
|View full text |Cite
|
Sign up to set email alerts
|

Aspects socioculturels de l’épilepsie dans une communauté rurale au nord Bénin en 2011

Abstract: Despite the development of knowledge in diagnosis and therapeutic of epilepsy it remains to be cause of rejection and stigma. We aimed to study the knowledge, attitude and practice toward epilepsy and the stigma in a rural community. The cross-sectional study was carried out from 1st to 31st March 2011 in a rural community (Tourou) at Parakou in the northern Benin. It was a door-to-door survey and included 1 031 adults older than 15 years. The diagnosis of epilepsy was based on International League Against Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
4
6
0
Order By: Relevance
“…African population still believe that epilepsy is a contagious disease, as we showed in our study. Similar results have been reported in Benin [25], Burkina Faso [26] and Burundi [27]. We also found comparable representations of the relation between epilepsy and alcohol [25] or genetic predisposition [28].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…African population still believe that epilepsy is a contagious disease, as we showed in our study. Similar results have been reported in Benin [25], Burkina Faso [26] and Burundi [27]. We also found comparable representations of the relation between epilepsy and alcohol [25] or genetic predisposition [28].…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been reported in Benin [25], Burkina Faso [26] and Burundi [27]. We also found comparable representations of the relation between epilepsy and alcohol [25] or genetic predisposition [28]. A study in urban areas of the CAR found that 28.8% believed that epilepsy was due to bad luck, and 45.0% to an evil spirit [4,29].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[ 13 14 ] Strictly speaking, they usually have difficulty in employment, education, socialization, and reproductive life. [ 14 15 16 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is a common neurological disorder with multiple and often curable causes [1]. Epilepsy affects approximately 50 million people worldwide making it the most common neurological disorder globally [2].…”
Section: Introductionmentioning
confidence: 99%